Is Same-Day Discharge After Minimally Invasive Myomectomy a Safe Option? [86]. (May 2015) - Alton, Katie; Sullivan, Shannon; Udaltsova, Natalia; Yamamoto, Miya; Zaritsky, Eve
Abstract : INTRODUCTION: Increasingly, myomectomies are routinely being completed with minimally invasive technology, either robotically or laparoscopically. Traditionally, many patients stay 1-2 days after this surgery. To date, no studies have evaluated whether patients can be safely discharged the same day after a minimally invasive myomectomy. Our primary objective was to evaluate readmission rates of patients discharged home the same-day following minimally invasive myomectomy. Secondary objectives included postoperative urgent care visits, as well as patient and operative characteristics. METHODS: This was a retrospective case series of patients discharged home the same day after laparoscopic or robotic myomectomy in a managed care setting in 2011-2013. Chart review was performed for outcomes of interest which included readmission rates, emergency department, and urgent clinic visits within 48 hours and 3 months, and surgical and demographic characteristics. RESULTS: Four hundred three minimally invasive myomectomies were performed during the study period. Eighty-eight percent (n=356) of patients were discharged home the same day; of those, 83% (n=297) of myomectomies were performed laparoscopically, and 17% (n=59) were performed robotically. The most common indication for myomectomy was pain (70%) and bleeding (46%). Two patients (0.6%) were readmitted within 48 hours, both from the laparoscopic group. A total of 5 patients (1.4%) were readmitted within 3 months; 4 from the laparoscopic group and 1 from the robotic group. Urgent care visits occurred in 3.9% of patients (n=14). Median myoma weight was 207 g, median body mass index was 26, median blood loss was 50 mL, and median surgical time was 150 minutes. CONCLUSION: Same-day discharge after laparoscopic or robotic myomectomy was found to have a low readmission rate and low health care utilization use in the immediate postoperative period. Same-day discharge appears to be a safe option for healthy patients undergoing minimally invasive myomectomy.